Pengaruh Pupuk Organik Cair (Poc) Air Leri terhadap Pertumbuhan Pisang Barangan Merah (Musa Acuminata Colla) - Sasti, Indri Dwi; Ramadhan, Eriska Wilda; Sembiring, Desi Sri Pasca Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Liquid organic fertilizer is a nutrient-rich solution produced from the decomposition of organic materials, including agricultural waste such as rice washing water (leren water). Red Barangan Banana (Musa acuminata colla) is a leading commodity in North Sumatra with high economic value, known for its sweet taste and soft texture. This study aims to examine the effect of rice washing water POC on the growth of Red Barangan Banana. The method used was a quantitative experiment with four variations of POC doses: P0 (0 ml/L), P1 (150 ml/L), P2 (300 ml/L), and P3 (450 ml/L). The observed parameters included stem diameter, plant height, and leaf length and width. The results showed that the P3 dose (450 ml/L) provided the best growth, with a stem diameter of 8.44 cm, plant height of 22.38 cm, leaf length of 24.93 cm, and leaf width of 11.29 cm. Overall, rice washing water POC proved effective in enhancing plant growth, particularly in stem diameter, plant height, and leaf length. This study encourages the utilization of agricultural waste as a sustainable natural nutrient source for farmers and the agricultural industry.